High-Dose Rate Salvage Interstitial Brachytherapy: A Case-Based Guide to the Treatment of Therapeutically Challenging Recurrent Vulvar Cancer - Hughes, Kelly Eileen; McLaughlin, Christopher M.; Fields, Emma C. (Frontiers in Oncology, 2017)
Vulvar cancer is a rare gynecological malignancy with incidence rates steadily increasing over the past 10 years. Despite aggressive treatment, recurrent disease is common. Vulvar cancer recurrence poses a significant therapeutic challenge as most patients have been previously treated with surgery and/or radiation limiting the options for additional treatment. There are no consensus guidelines for the treatment of recurrent disease. Current literature supports the use of salvage interstitial brachytherapy. However, the total sample size is small. The goal of this case report is to review the current literature and to provide a guide for the use of salvage interstitial brachytherapy for recurrent disease by describing, in detail, the techniques used to treat two patients with unique cases of vulvar cancer recurrences in women with advanced disease and multiple medical comorbidities.